EFFECTIVE LEADERSHIP: THE FERGUSON WAY - TOMA SORIN-GEORGE (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Todays’ globalized business world is characterized by hypercompetition and uncessant changes. On the one hand, hypercompetition imposes business organizations worldwide to provide high quality and innovative products and/or services. On the other hand, numerous and often unexpected changes require strong leadership. Thus, there is a significant effect of organization resources, such as leadership, on gaining sustained competitive advantage in any domain of activity, either business or football). The aims of the paper are to define the concept of leadership, present the features of effective leadership and briefly analyse the successful way Sir Alex Ferguson managed one of the famous football clubs in the world, Manchester United. In this respect, the author employed a qualitative research method. The results of this study show that the concept of leadership has many facets and is rather difficult to be defined. Also, it emphasizes the features of effective leadership and exemplifies them in the case of Sir Alex Ferguson, one of the most successful football managers all over the world.